2018
DOI: 10.1016/j.clinph.2017.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of independent component analysis for accurate pathological ripple detection in intracranial EEG recordings recorded extra- and intra-operatively

Abstract: Objective To develop and validate a detector that identifies ripple (80–200 Hz) events in intracranial EEG (iEEG) recordings in a referential montage and utilizes independent component analysis (ICA) to eliminate or reduce high-frequency artifact contamination. Also, investigate the correspondence of detected ripples and the seizure onset zone (SOZ). Methods iEEG recordings from 16 patients were first band-pass filtered (80–600 Hz) and Infomax ICA was next applied to derive the first independent component (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 41 publications
(51 reference statements)
0
40
0
Order By: Relevance
“…One-second trials of ripples occurring on inter-ictal discharges were identified using a previously described algorithm (Weiss et al, 2016b; Shimamoto et al, 2018). In brief, (1) INFOMAX independent component analysis (Bell and Sejnowski, 1997) was applied to referential recordings to reduce muscle contamination, and demarcate artefactual ripple events produced by muscle contamination (2) ripples were detected using a Hilbert detector applied to the band-pass filtered and ICA processed signal, (3) for each ripple detected a one-second trial was generated with a ripple centered at 0.5 s, (4) To distinguish ripples that occur during epileptiform spikes from all other ripples, we utilized a validated method (Shimamoto et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One-second trials of ripples occurring on inter-ictal discharges were identified using a previously described algorithm (Weiss et al, 2016b; Shimamoto et al, 2018). In brief, (1) INFOMAX independent component analysis (Bell and Sejnowski, 1997) was applied to referential recordings to reduce muscle contamination, and demarcate artefactual ripple events produced by muscle contamination (2) ripples were detected using a Hilbert detector applied to the band-pass filtered and ICA processed signal, (3) for each ripple detected a one-second trial was generated with a ripple centered at 0.5 s, (4) To distinguish ripples that occur during epileptiform spikes from all other ripples, we utilized a validated method (Shimamoto et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In brief, (1) INFOMAX independent component analysis (Bell and Sejnowski, 1997) was applied to referential recordings to reduce muscle contamination, and demarcate artefactual ripple events produced by muscle contamination (2) ripples were detected using a Hilbert detector applied to the band-pass filtered and ICA processed signal, (3) for each ripple detected a one-second trial was generated with a ripple centered at 0.5 s, (4) To distinguish ripples that occur during epileptiform spikes from all other ripples, we utilized a validated method (Shimamoto et al, 2018). We calculated the derivative of the peri-ripple band-pass filtered (4–30 Hz) iEEG and applied a threshold of 4 μV/msec.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent processing steps for those recordings from macroelectrodes deemed suitable on the basis of visual inspection using BESA v5 (Gräfelfing, Germany) were performed using custom software developed in Matlab. Muscle and electrode artifacts in iEEG recordings from were reduced using a custom independent component analysis (ICA)-based algorithm 20,21 . After applying this ICA-based method, ripples were detected in the referential montage iEEG recordings per contact by utilizing a Hilbert detector 20 , in which (i) applied a 1000th order symmetric finite impulse response (FIR) band-pass filter (80–600 Hz), and (ii) applied Hilbert transform to calculate the instantaneous amplitude of this time series according to the analytic signal z(t), described in Eqn.…”
Section: Methodsmentioning
confidence: 99%
“…Given that pHFOs have largely been identified by direct brain recording, the majority of studies confirming their reliability as a biomarker of epilepsy have been limited to identification of the epileptogenic region for surgery, which is discussed in detail in the next chapter (J. Wu this issue). Various aspects of HFOs, such as their occurrence on spikes and relationship to slow waves, have been used to distinguish pHFOs from normal HFOs, and novel approaches are utilized to identify false HFOs, and to improve automatic detection . Most importantly, however, for the future clinical application of pHFOs to diagnosis and treatment, and to predict patients at risk for epilepsy, work is being done to identify pHFOs noninvasively.…”
Section: Phfosmentioning
confidence: 99%
“…Various aspects of HFOs, such as their occurrence on spikes and relationship to slow waves, have been used to distinguish pHFOs from normal HFOs, and novel approaches are utilized to identify false HFOs, and to improve automatic detection. [22][23][24][25][26][27] Most importantly, however, for the future clinical application of pHFOs to diagnosis and treatment, and to predict patients at risk for epilepsy, work is being done to identify pHFOs noninvasively. Several studies have now reported the ability to record activity in the HFO frequency range from scalp electrodes, [28][29][30] but it is unclear whether these events are the same as those recorded directly from the brain.…”
Section: Key Pointsmentioning
confidence: 99%